2021
DOI: 10.15252/embr.202051400
|View full text |Cite
|
Sign up to set email alerts
|

Stable kinetochore–microtubule attachments restrict MTOC position and spindle elongation in oocytes

Abstract: In mouse oocytes, acentriolar MTOCs functionally replace centrosomes and act as microtubule nucleation sites. Microtubules nucleated from MTOCs initially assemble into an unorganized ball‐like structure, which then transforms into a bipolar spindle carrying MTOCs at its poles, a process called spindle bipolarization. In mouse oocytes, spindle bipolarization is promoted by kinetochores but the mechanism by which kinetochore–microtubule attachments contribute to spindle bipolarity remains unclear. This study dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
(97 reference statements)
3
7
0
Order By: Relevance
“…Therefore, although we can confirm that Aurora A phosphorylates NDC80 at uncongressed chromosomes during pole-based error correction ( Ye et al, 2015 ), we find this is maintained on chromosomes aligned to the metaphase plate. This finding is consistent with data in the main figures or supplemental data in other studies that also identify NDC80 pS55 on the kinetochores of aligned metaphase chromosomes ( Courtois et al, 2021 ; DeLuca et al, 2011 ; Posch et al, 2010 ; Schleicher et al, 2017 ; Suzuki et al, 2014 ). One study also reported NDC80 pS15, pS44, and pS55 staining in metaphase persisted at the same level into anaphase ( DeLuca et al, 2011 ), suggesting this is true for multiple sites in the NDC80 N-terminus rather than representing unique behavior of an individual site.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, although we can confirm that Aurora A phosphorylates NDC80 at uncongressed chromosomes during pole-based error correction ( Ye et al, 2015 ), we find this is maintained on chromosomes aligned to the metaphase plate. This finding is consistent with data in the main figures or supplemental data in other studies that also identify NDC80 pS55 on the kinetochores of aligned metaphase chromosomes ( Courtois et al, 2021 ; DeLuca et al, 2011 ; Posch et al, 2010 ; Schleicher et al, 2017 ; Suzuki et al, 2014 ). One study also reported NDC80 pS15, pS44, and pS55 staining in metaphase persisted at the same level into anaphase ( DeLuca et al, 2011 ), suggesting this is true for multiple sites in the NDC80 N-terminus rather than representing unique behavior of an individual site.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, although we can confirm that Aurora A phosphorylates NDC80 at uncongressed chromosomes during pole-based error correction (Ye et al, 2015), we find this is maintained on chromosomes aligned to the metaphase plate. This finding is consistent with data in the main figures or supplemental data other studies that also identify NDC80 pS55 on the kinetochores of aligned metaphase chromosomes (Courtois et al, 2021; DeLuca et al, 2011; Posch et al, 2010; Schleicher et al, 2017; Suzuki et al, 2014). One study also reported NDC80 pS15, pS44 and pS55 staining in metaphase persisted at the same level into anaphase (DeLuca et al, 2011), suggesting this is true for multiple sites in the NDC80 N-terminus rather than representing unique behavior of an individual site.…”
Section: Resultssupporting
confidence: 93%
“…Kinetochores drive the first mode until the gradual increase in CDK1 activity stabilizes microtubule attachment 13,16 , which reduces MPS1 activity at kinetochores 34,35 , allowing kinetochores to switch to the second mode. In the second mode, kinetochores employ stably attached microtubules, which maintains the integrity of the bipolar spindle by restricting microtubule organizing centers at the poles and preventing excessive spindle elongation during late prometaphase and metaphase 28 . In oocytes lacking MPS1 activity, the first mode is absent and thus spindle bipolarization is delayed, while increased CDK1 activity stabilizes microtubules attached to kinetochores from random directions.…”
Section: Discussionmentioning
confidence: 99%